2012
DOI: 10.1161/circresaha.111.246108
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Impaired Mitochondrial Autophagy to Cardiac Aging

Abstract: The prevalence of cardiovascular disease (CVD) increases with advancing age. While the long-term exposure to cardiovascular risk factors plays a major role in the etiopathogenesis of CVD, intrinsic cardiac aging enhances the susceptibility to developing heart pathologies in late life. The progressive decline of cardiomyocyte mitochondrial function is considered to be a major mechanism underlying heart senescence. Damaged mitochondria not only produce less ATP, but also generate increased amounts of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(165 citation statements)
references
References 138 publications
(201 reference statements)
5
157
0
3
Order By: Relevance
“…Mitochondrial dysfunction and mitochondria oxidative stress have linked to age-related heart diseases. [36][37][38][39] To examine the effects of age on heart function of Gab1-cKO mice, we continued to monitor cardiac function of Gab1-WT and Gab1-cKO mice via echocardiography as they aged from 4 weeks to 6 months. We found that at 3 months of age, Gab1-cKO mice exhibited a decreased EF and increased LVIDd, without obvious morphological changes and no apparent differences in LVPW compared with Gab1-WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction and mitochondria oxidative stress have linked to age-related heart diseases. [36][37][38][39] To examine the effects of age on heart function of Gab1-cKO mice, we continued to monitor cardiac function of Gab1-WT and Gab1-cKO mice via echocardiography as they aged from 4 weeks to 6 months. We found that at 3 months of age, Gab1-cKO mice exhibited a decreased EF and increased LVIDd, without obvious morphological changes and no apparent differences in LVPW compared with Gab1-WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…2013; Palmer et al ., 2015). Interestingly, HF is associated with similar cellular perturbations, which suggests that HF could be considered as an accelerated form of aging (Dutta et al ., 2012; Wohlgemuth et al ., 2014). Thus, it is possible that the processes that underlie both frailty and HF could each perturb homeostasis to lead to low‐level chronic inflammation.…”
Section: How Aging Frailty and Hf Interact To Induce Inflammationmentioning
confidence: 99%
“…The clamps were then removed, and the incisions were closed. Rats were euthanized at 0, 3,6,12,24,48, and 72 h after surgery (n ϭ 5 rats/group). The left kidney was rapidly removed and processed for histological evaluation, protein extraction, and RNA extraction, as previously described (38,40).…”
Section: Induction Of Akimentioning
confidence: 99%